Clonal expansions in ulcerative colitis identify patients with neoplasia - Salk, Jesse J; Salipante, Stephen J; Risques, Rosa Ana; Crispin, David A; Li, Lin; Bronner, Mary P; Brentnall, Teresa A; Rabinovitch, Peter S; Horwitz, Marshall S; Loeb, Lawrence A (Proceedings of the National Academy of Sciences - PNAS, 2009)
Chronic inflammation predisposes to a variety of human cancers. Affected tissues slowly accumulate mutations, some of which affect growth regulation and drive successive waves of clonal evolution, whereas a far greater number are functionally neutral and serve only to passively mark expanding clones. Ulcerative colitis (UC) is an inflammatory bowel disease, in which up to 10% of patients eventually develop colon cancer. Here we have mapped mutations in hypermutable intergenic and intronic polyguanine tracts in patients with UC to delineate the extent of clonal expansions associated with carcinogenesis. We genotyped colon biopsies for length altering mutations at 28 different polyguanine markers. In eight patients without neoplasia, we detected only two mutations in a single individual from among 37 total biopsies. In contrast, for 11 UC patients with neoplasia elsewhere in the colon, we identified 63 mutations in 51 nondysplastic biopsies, and every patient possessed at least one mutant clone. A subset of clones were large and extended over many square centimeters of colon. Of these, some occurred as isolated populations in nondysplastic tissue, considerably distant from neoplastic lesions. Other large clones included regions of cancer, suggesting that the tumor arose within a preexisting clonal field. Our results demonstrate that neutral mutations in polyguanine tracts serve as a unique tool for identifying fields of clonal expansions, which may prove clinically useful for distinguishing a subset of UC patients who are at risk for developing cancer.